Fusion of Visible Light Indoor Positioning and Inertial Navigation Based on Particle Filter - Zhitian Li; Aiying Yang; Huichao Lv; Lihui Feng; Wenzhan Song (IEEE Photonics Journal, 2017)
With the increasing demand for indoor positioning-based services, indoor positioning methods based on Bluetooth, Wi-Fi, ultra wide band (UWB), inertial navigation, and visual light communications (VLC) have been proposed. Considering the limitations of accuracy, cost and complexity, we propose a fusion positioning scheme integrating VLC positioning and inertial navigation base on particle filter. The experimental results demonstrated that the performance degradation caused by the multipath effect and light obstruction in VLC-based positioning and the cumulative error associated with inertial navigation are solved in the proposed fusion system. The accuracy of the fusion positioning system is in centimeters, which is two to four times better as compared to the VLC-based positioning or inertial navigation alone. Furthermore, the fusion positioning system has the advantages of high accuracy, energy saving, low cost, and easy to install, making it a promising candidate for future indoor positioning applications.